Important functional role of the protein osteopontin in the progression of malignant pleural mesothelioma - Digifico, Elisabeth; Erreni, Marco; Mannarino, Laura; Marchini, Sergio; Ummarino, Aldo; Anfray, Clément; Bertola, Luca; Recordati, Camilla; Pistillo, Daniela; Roncalli, Massimo; Bossi, Paola; Zucali, Paolo Andrea; et al. (Frontiers in Immunology, 2023)
Background: Malignant Pleural Mesothelioma (MPM) is an aggressive cancer of the mesothelial lining associated with exposure to airborne non-degradable asbestos fibers. Its poor response to currently available treatments prompted us to explore the biological mechanisms involved in its progression. MPM is characterized by chronic non-resolving inflammation. in this study we investigated which inflammatory mediators are mostly expressed in biological tumour samples from MPM patients. Methods: Expression and quantification of Osteopontin (OPN) was detected in tumour and plasma samples of MPM patients by mRNA, immunohistochemistry and ELISA. The functional role of OPN was investigated in mouse MPM cell lines in vivo using an orthotopic syngeneic mouse model. Results: In patients with MPM, the protein OPN was significantly more expressed in tumours than in normal pleural tissues and predominantly produced by mesothelioma cells; plasma levels were elevated in patients and associated with poor prognosis. However, modulation of OPN levels was not significantly different in a series of 18 MPM patients receiving immunotherapy with durvalumab alone or with pembrolizumab in combination with chemotherapy, some of whom achieved a partial clinical response. Two established murine mesothelioma cell lines: AB1 and AB22 of sarcomatoid and epithelioid histology, respectively, spontaneously produced high levels of OPN. Silencing of the OPN gene (Spp1) dramatically inhibited tumour growth in vivo in an orthotopic model, indicating that OPN has an important promoting role in the proliferation of MPM cells. Treatment of mice with anti-CD44 mAb, blocking a major OPN receptor, significantly reduced tumour growth in vivo. Conclusions: These results demonstrate that OPN is an endogenous growth factor for mesothelial cells and inhibition of its signaling may be helpful to restrain tumour progression in vivo. These findings have translational potential to improve the therapeutic response of human MPM